Doctoral Students' Perspectives on Their Training as Teachers in Higher Education. Issue 3 (3rd July 2019) - Boyce, B. Ann; Lund, Jackie L.; Napper-Owen, Gloria; Almarode, Danielle
ABSTRACT: The purpose of this article was to examine Kinesiology Doctoral Students' (DS) perspectives on their pedagogical training received during doctoral study. Using the Kinesiology Doctoral Student (KDS) survey, 121 current and past DS provided information on nine different items related to teacher training. Specifically, these items consisted of measures of: (a) enjoyment, (b) clear understanding of teaching responsibilities, (c) ability to teach a lecture, (d) preparedness to teach a lab course, (e) ability to teach specialized graduate courses, (f) ability to address diversity issues, (g) preparedness to advise undergraduates, and (h) preparedness to advise graduate students. This topic was viewed through three lenses: (a) status (past and current DS), (b) gender, and (c) sub-disciplines (social and behavioral sciences [SBS] research and health/hard sciences [HS] research). The following statistical significant findings were revealed: (a) SBS participants had a clearer understanding of their teaching responsibilities than HS participants, (b) SBS participants perceived a significant higher ability to teach lecture and laboratory courses compared to HS participants, (c) SBS participants had significantly higher perceptions of their ability to address diversity than HS participants, and (d) current participants felt more prepared to advise both graduate and undergraduate students than their past participant counterparts.